KEANEKARAGAMAN TUMBUHAN MANGROVE DI TAMAN NASIONAL BALI BARAT - Arinasa, Ida Bagus Ketut (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2012)
The diversity of mangrove at West Bali National Park has not been reported completely. The exploration was conducted from 12 - 16 June, 2011 from Banyuwedang to Gilimanuk and from Gilimanuk to Sumbersari-Melaya mangrove forests. The result showed that 18 families consist of 21 genera and 28 mangrove species were recorded at West Bali National Park, these are 11,5% of the Indonesian mangroves.